The Existence of Arab Tourism Village in Gresik: A Historical Study of the Pandemic as a Foundation for Navigating Post-Covid-19 at the Religious Tourism Destination in Arab Tourism Village, Gresik: Eksistensi Kampung Wisata Arab Gresik: Studi Historis Pandemi Sebagai Bekal Menjalani Post Covid-19 Pada Destinasi Wisata Religi di Kampung Wisata Arab Gresik - Santoso , Yuniawan Heru; Nuruddin, Nuruddin; Fiatiano, Edwin; Ismail, Muhammad Husein (Jurnal Ilmiah Hospitality Management, 2024)
This study examines the resilience and recovery of the Arab Tourism Village in Gresik, focusing on the impact of the Covid-19 pandemic and the strategies implemented for post-pandemic recovery. The village, renowned for its Arab Kampong in Gapurosukolilo, is home to the graves of the first harbor master and the first regent of Gresik, which have become significant cultural heritage and pilgrimage tourism sites. However, during the pandemic, tourism in the area was severely affected, with a significant decline in visitor numbers and a substantial reduction in the local community's income.  Using a qualitative historical approach, the research analyzes documents and interviews regarding the impact of the pandemic and the subsequent efforts to recover. The findings indicate that the pandemic served as a critical period for reflection and adaptation in the village's tourism sector. Strategies focused on improving health and safety standards, promoting virtual religious tourism experiences, and developing new marketing initiatives. The village embraced the processes of rethink, rebuild, and restart, leading to the implementation of strategic programs aimed at helping the community navigate the post-Covid-19 era effectively.  The urgency of this study lies in understanding how the pandemic can be used as an opportunity to rethink and rebuild sustainable tourism models for cultural and religious destinations. The novelty of the research is its focus on the Arab Tourism Village in Gresik, offering insights into how a historical, culturally rich area can adapt to the challenges of the post-pandemic tourism landscape. This study contributes to the broader discourse on tourism recovery, providing valuable lessons for similar religious and cultural tourism destinations.